ANALISIS KEBUTUHAN PENGEMBANGAN BUKU CERITA DWI BAHASA SEBAGAI UPAYA PELESTARIAN BAHASA DAERAH DAN MENINGKATKAN SIKAP PEDULI LINGKUNGAN SISWA SD - Heryaanto, Debi; Yusnia, Yusnia; Agusdianita, Neza; Rizqa Dwi Shofiya Maghfira Izzania; Devi Fitriani; Ramayani, Neti (Prosiding Temu Ilmiah Nasional Guru, 2026)
The development of bilingual storybooks as an effort to preserve local languages and enhance environmental awareness among elementary school students represents a strategic step in education. This research aims to analyze the need for instructional materials based on two languages, encompassing both a local language and the Indonesian language, through the Research and Development (R&D) method. The study focuses specifically on needs analysis, utilizing questionnaires and interviews conducted with students and teachers.The analysis results indicate a significant demand for books that integrate local vocabulary and cultural values, with 83% of respondents expressing this necessity. This finding suggests that storybooks covering environmental themes alongside local cultural elements can boost students' learning motivation and their attitude towards environmental care. In conclusion, the development of bilingual storybooks has substantial potential in supporting language learning and environmental awareness among the younger generation, underscoring the importance of support from educational institutions for the provision of high-quality instructional materials.